There should have been eight - Singh, Nalini, 1977- (Berkley, 2023)
"Seven friends. One last weekend. A mansion half in ruins. No room for lies. Someone is going to confess. Because there should've been eight... They met when they were teenagers. Now they're adults, and time has been kind to some and unkind to others--and the cruelest of all to Bea, the one they lost nine long years ago. They've gathered to reminisce at Bea's family estate, a once-glorious mansion straight out of a gothic novel. Best friends, old flames, secret enemies, and new lovers are all under one roof. But when the weather turns and they're snowed in at the edge of eternity, there's nowhere left to hide from their shared history. As the walls close in, the pretense of normality gives way to long-buried grief, bitterness, and rage. Underneath it all, there's the nagging feeling that Bea's shocking death wasn't what it was claimed to be. And before the weekend is through, the truth will be unleashed--no matter the cost..."--